Fabrication and Physiochemical Properties of Alginate and Fish Gelatin Biofilm for Wound Healing Application - Rethnam, Kirubaneeswary; Dr. MAIZLINDA IZWANA BINTI IDRIS (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This research focuses on developing and evaluating alginate and fish gelatin biofilms for wound healing applications. Wound management remains a significant challenge in healthcare, requiring innovative solutions to accelerate healing and minimize complications. The study highlights the biocompatibility, biodegradability, and wound-healing potential of alginate and fish gelatin. Biofilms were fabricated using a casting method with various alginate-to-fish gelatin ratios (100:0, 95:5, 85:15, 80:20, and 75:25) and cross-linking to enhance properties. The resulting films were characterized using FTIR, AFM, SEM, and contact angle measurements. FTIR validated the effective combination of alginate and fish gelatin, whereas SEM and AFM evaluations indicated that a higher fish gelatin concentration enhanced surface shape and roughness. Contact angle assessments showed good hydrophilicity, supporting a moist wound environment. The biofilms demonstrate advantageous characteristics that fulfill the criteria for wound healing materials.